2007
DOI: 10.2337/db06-0734
|View full text |Cite
|
Sign up to set email alerts
|

Human Islet Amyloid Polypeptide Oligomers Disrupt Cell Coupling, Induce Apoptosis, and Impair Insulin Secretion in Isolated Human Islets

Abstract: Insulin secretion from the 2,000 -3,000 ␤-cells in an islet is a highly synchronized activity with discharge of insulin in coordinate secretory bursts at approximately 4-min intervals. Insulin secretion progressively declines in type 2 diabetes and following islet transplantation. Both are characterized by the presence of islet amyloid derived from islet amyloid polypeptide (IAPP). In the present studies, we examined the action of extracellular human IAPP (h-IAPP) on morphology and function of human islets. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 46 publications
4
155
0
Order By: Relevance
“…Intracellular amyloid-like aggregates have also been reported in human and hIAPP-overexpressing transgenic mouse islets transplanted into type 1 diabetic mice [4,9,44,45] hIAPP aggregates appear to be more toxic than large fibrils and are probably the major mediators of beta cell death [19][20][21]46]. Despite convincing evidence implicating a membrane interaction in the cytotoxicity of exogenous synthetic hIAPP aggregates [19,46,47], the mode of this interaction is still unclear. Our studies show that prevention of hIAPP aggregation and interaction with beta cells by the amyloid-binding dye Congo Red, markedly reduces caspase-3 activation and apoptosis in INS-1 beta cells, supporting the notion that interaction of extracellular hIAPP aggregates with beta cell membranes induces caspase-3 activation and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Intracellular amyloid-like aggregates have also been reported in human and hIAPP-overexpressing transgenic mouse islets transplanted into type 1 diabetic mice [4,9,44,45] hIAPP aggregates appear to be more toxic than large fibrils and are probably the major mediators of beta cell death [19][20][21]46]. Despite convincing evidence implicating a membrane interaction in the cytotoxicity of exogenous synthetic hIAPP aggregates [19,46,47], the mode of this interaction is still unclear. Our studies show that prevention of hIAPP aggregation and interaction with beta cells by the amyloid-binding dye Congo Red, markedly reduces caspase-3 activation and apoptosis in INS-1 beta cells, supporting the notion that interaction of extracellular hIAPP aggregates with beta cell membranes induces caspase-3 activation and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…IAPP is produced in the β-cells and inhibits insulin secretion (14)(15)(16). IAPP of the human form may form fibrils leading to islet amyloid deposition, β-cell dysfunction and type 2 diabetes (17,18). We have previously shown that mice with β -cell specific overexpression of hIAPP have severe glucose intolerance and defective insulin response to gastric glucose (12).…”
Section: Introductionmentioning
confidence: 99%
“…In type II diabetes, IAPP forms amyloid deposits that are correlated with ␤-cell death (16). Recent transgenic models, e.g., the HIP rat, strongly support a role for IAPP in diabetic pathology (17). Residues 20-29 of IAPP, SNNFGAILSS, referred to here as IAPP [20][21][22][23][24][25][26][27][28][29] , have previously been shown to form amyloid independently of the rest of the sequence (18)(19)(20).…”
mentioning
confidence: 99%